2022
DOI: 10.1002/acp.3944
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a short computerized growth mindset intervention with implementation intentions on French students entering university

Abstract: The goal of this study is to test the effect of a growth mindset (GM) intervention with an added implementation intentions (II) protocol on French first‐year university students' mindset, creating a new type of psychosocial intervention (GMII). We exposed participants to 3 intervention conditions (GMII vs. GM vs. control), measured mindset via self‐reported measures during 3 stages (online questionnaire 2 weeks before the intervention; experimental session with exposure to the intervention; online questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Four studies investigated single‐session growth‐mindset building education interventions on students' growth‐mindset 62,79–81 . Meta‐analysis of two trials with 206 participants (Figure 2c) showed growth‐mindset interventions improved mindset by a small amount (pooled SMD 0.25 95%CI −0.18 to 0.68, I 2 55%) compared to no‐intervention; however, the 95%CI crossed zero 62,79 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies investigated single‐session growth‐mindset building education interventions on students' growth‐mindset 62,79–81 . Meta‐analysis of two trials with 206 participants (Figure 2c) showed growth‐mindset interventions improved mindset by a small amount (pooled SMD 0.25 95%CI −0.18 to 0.68, I 2 55%) compared to no‐intervention; however, the 95%CI crossed zero 62,79 .…”
Section: Resultsmentioning
confidence: 99%
“…62,[79][80][81] Metaanalysis of two trials with 206 participants (Figure 2c) showed growth-mindset interventions improved mindset by a small amount (pooled SMD 0.25 95%CI À0.18 to 0.68, I 2 55%) compared to nointervention; however, the 95%CI crossed zero. 62,79 The GRADE certainty of evidence for this analysis was very low after downgrading for risk of bias, inconsistency and imprecision (Table 2). Single-group studies report similar small shifts towards a growth-mindset following the intervention.…”
Section: Effects Of Intervention On Growth-mindsetmentioning
confidence: 99%
“…They have to use the arguments presented in the text. These two exercises have been used in GM interventions in the past [ 4 , 19 , 20 ]. The VHS is presented following the GM article.…”
Section: Discussionmentioning
confidence: 99%
“…The intervention combined existing behavior change theories and strategies, namely growth mindset theory (GM—[ 2 ]) and implementation intentions (II—[ 3 ]). This type of intervention, labeled GMII (i.e., Growth Mindset and Implementation Intentions), was original and thought to be able to foster motivation and changes among individuals [ 4 ]. The present GMII intervention was created using both empirical qualitative and quantitative data and input from the scientific literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation